A Novel Device for Grasping Assessment during Functional Tasks: Preliminary Results - Rocha, Ana Carolinne Portela; Tudella, Eloisa; Pedro, Leonardo M.; Appel, Viviane Cristina Roma; da Silva, Louise Gracelli Pereira; Caurin, Glauco Augusto de Paula (Frontiers in Bioengineering and Biotechnology, 2016)
This paper presents a methodology and first results obtained in a study with a novel device that allows the analysis of grasping quality. Such a device is able to acquire motion information of upper limbs allowing kinetic of manipulation analysis as well. A pilot experiment was carried out with six groups of typically developing children aged between 5 and 10 years old, with 7-8 children in each one. The device, designed to emulate a glass, has an optical system composed by one digital camera and a special convex mirror that together allow image acquisition of grasping hand posture when it is grasped and manipulated. It also carries an Inertial Measurement Unit (IMU) that captures motion data as acceleration, orientation, and angular velocities. The novel instrumented object is used in our approach to evaluate functional tasks performance in quantitative terms. During tests each child was invited to grasp the cylindrical part of the device that was placed on the top of a table, simulating the task of drinking a glass of water. In the sequence the child was oriented to transport the device back to the starting position and release it. The task was repeated 3 times for each child. A grasping hand posture evaluation is presented as an example to evaluate grasping quality. Additionally, motion patterns obtained with the triasl performed with the different groups are presented and discussed. This device is attractive due to its portable characteristics, the small size and its ability to evaluate grasping form. The results may be also useful to analyze the evolution of the rehabilitation process through reach-to-grasping movement and the grasping images analysis.